2008
DOI: 10.1007/s10152-008-0125-8
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the invasive Pacific oyster Crassostrea gigas during the early stages of an outbreak in the Wadden Sea (Germany)

Abstract: Since the late 1990s, the Pacific oyster (Crassostrea gigas) has spread into the East Frisian Wadden Sea (Germany). This invasion provided an opportunity to study the population dynamics and the patterns of spread during the initial bioinvasion process. With its source area in The Netherlands, the bioinvasion continues in an eastward direction, as documented by a gradient of high abundances in the west and low abundances in the east during the first study year. One year later, abundances of the Pacific oyster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 40 publications
(76 reference statements)
2
39
0
1
Order By: Relevance
“…From these results it can be concluded that the Pacific oyster increased explosively between 2003 and 2005, but it seems to have stabilised since then. A comparably fast increase has also been found in the German Wadden Sea Brandt et al 2008;Schmidt et al 2008). (Fig.…”
Section: Current Status Of the Pacific Oyster In The Dutch Wadden Seasupporting
confidence: 55%
See 1 more Smart Citation
“…From these results it can be concluded that the Pacific oyster increased explosively between 2003 and 2005, but it seems to have stabilised since then. A comparably fast increase has also been found in the German Wadden Sea Brandt et al 2008;Schmidt et al 2008). (Fig.…”
Section: Current Status Of the Pacific Oyster In The Dutch Wadden Seasupporting
confidence: 55%
“…Oysters seem to grow up to 4 cm in the first year (this study ;Cadée 2000;Reise 1998;Wehrmann et al 2000;Schmidt et al 2008). Cadée (2000) also measured growth of second year oysters in the Mokbaai (Texel).…”
Section: Reproduction and Individual Growth Of Pacific Oystersmentioning
confidence: 56%
“…Ainsi, en France, la rade de Brest et d'autres secteurs de Bretagne Sud et Vendée, qui ne connaissaient qu'un captage limité les années favorables sont maintenant en état de soutenir l'ostréiculture bretonne par la fourniture de naissains. La Wadden See (néerlandaise et allemande) a été colonisée dès 1980 (Diederich et al 2005, Schmidt et al 2008. En 2010, le Danemark, la Suède et la Norvège (Wrange et al 2010) voient des populations de Crassostrea gigas s'installer.…”
Section: Carte Des Mouvements Par La Route Des Naissains D'huîtres Jaunclassified
“…Biological invasions consist of human induced species translocation such as global shipping and aquaculture or of natural range expansions (Schmidt et al, 2008). Venerupis aurea (Gmelin, 1791) is endemic to the Mediterranean Sea and have penetrated through the Suez Canal and successfully colonized Lake Timsah (Fouda and Abou Zied, 1990).…”
Section: Introductionmentioning
confidence: 99%